2017
DOI: 10.1016/j.apsusc.2016.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Controlled hydrodynamic conditions on the formation of iron oxide nanostructures synthesized by electrochemical anodization: Effect of the electrode rotation speed

Abstract: Iron oxide nanostructures are of particular interest because they can be used as photocatalysts in water splitting due to their advantageous properties. Electrochemical anodization is one of the best techniques to synthesize nanostructures directly on the metal substrate (direct back contact). In the present study, a novel methodology consisting of the anodization of iron under hydrodynamic conditions is carried out in order to obtain mainly hematite (α-Fe 2 O 3) nanostructures to be used as photocatalysts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…A large variety of different synthesis procedures have been used for preparing hematite nanostructures. One approach is anodization which allows synthesizing self-organizing nanostructures, such as nanotubes, on a Fe metal substrate [24][25][26][27]. Another method is thermal oxidation of iron, which is simple and cheap [28,29], and where hematite nanowhiskers and nanowires can be grown from metal substrates.…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of different synthesis procedures have been used for preparing hematite nanostructures. One approach is anodization which allows synthesizing self-organizing nanostructures, such as nanotubes, on a Fe metal substrate [24][25][26][27]. Another method is thermal oxidation of iron, which is simple and cheap [28,29], and where hematite nanowhiskers and nanowires can be grown from metal substrates.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, thickness of the nanostructures were measured, and they were comprised between 810 and 870 nm in all cases, which indicated that rotation speed does not affect the thickness of the synthesized nanostructures [69].…”
Section: Structural Characterizationmentioning
confidence: 88%
“…This morphology results in less photoactivity since light irradiation cannot go deep into the nanotubes. On the other hand, when rotation speed is 3000 rpm (see Figure 14d), the morphology is a mixture between what occurs at 0 and 2000 rpm, that is, the nanotubes are collapsed and stacked and an initiation layer appears in some parts of the nanostructure covering the tubes [69]. Hence, illumination is not effective in this case, and the photoactivity is affected.…”
Section: Structural Characterizationmentioning
confidence: 98%
“…Literature is quite extensive about the surface treatments carried out to date [1][2][3][4][5][6]. Nevertheless, the anodizing process that was initially developed for aluminum alloys [7,8] and later for other metals, such as Mg [9], Ga [10], Co [11], W [12], Nb [13], Zr [14], Sn [15], and Ti [16,17], has emerged as a new alternative to surface functionalization of iron base alloys of particular interest in fields such as photocatalysis, sensors, corrosion, environmental remediation, and biomedical to name a few [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have studied the growth of anodic layers on stainless steels, being 316L [25,26] and 304 [27][28][29][30] the most commonly used. The studies on 316L SS indicate that the addition of water to organic baths improves the diameter and thickness of the grown layers [37].…”
Section: Introductionmentioning
confidence: 99%